Desenvolvimento de uma plataforma virtual em telecirurgia como ferramenta complementar de ensino - Cardoso, Ricardo Bertoglio (2014)
The constant evolution of technology enables a wider access to and a more global production of digital texts, audios, images, and videos. The internet, which greatly enhances this sharing capability, has been constantly growing in coverage and in data transfer capacity, therefore allowing virtual communication to simulate real-life interaction. The combination of these elements in education, especially in health education, led to large improvements in the capacity to illustrate it rather than just explain it. These technologies have great potential to improve teaching methods, which sometimes are inefficient or have high maintenance costs. In the theoretical learning of surgical procedures, for example, the presence of students in the operating room does not necessarily provide them with a better understanding of the technique used by the surgeon, as he or she may not be able to get close enough to see the area where the procedure is being performed. This problem stems from the limited space available in the room, as well as from the care for the patient s wellbeing, which should not be compromised as result of the amount of observers in the room. Aware of these elements and of the existing demand for improvement of teaching tools in the university, this project had as its main aim the development of a telesurgery system for health education. In order to accomplish this goal, three systems were developed: a photograph camera positioning equipment (eSurg-Arm) to assist image acquisition in the operating room; a specification of equipment and video formats to enable image acquisition and transmission (eSurg-Video), and a health education web platform (eSurg-Web). The eSurg-Arm successfully developed the design, the simulation, the prototyping, and the testing of hardware, software, and mechanical devices and parts. The development of eSurg-Video called for the analysis of different video compression and transmission technologies. The making of eSurg-Web established the parameters (i.e. functionalities and information) to build a distance education web-learning tool, as well as to develop a functional prototype. Each of these systems accomplished different results. The eSurg-Arm built and validated three systems: movement control and instrumentation, articulated arm and Pan/Tilt/Roll/Zoom. The eSurg-Video enabled the synchronous and asynchronous video streaming of different resolution videos. The eSurg-Web accomplished the design of multiple information blocks, which enabled the development of an educational web platform. In short, the eSurg project successfully positioned an image acquisition system and granted access to a web platform that allow professors and students to interact with surgical multimedia content from medical/chirurgical procedures performed at the São Lucas Hospital PUCRS.